Food preferences and intake in a population of Dutch individuals with self-reported smell loss: An online survey. (January 2020) - Postma, E.M.; De Graaf, C.; Boesveldt, S.
Highlights: Food preferences and intake of patients with smell loss were compared to controls. Participants with acquired smell loss had no major changes in food preferences. Participants with congenital smell loss had more taste-oriented preferences. Adherence to dietary guidelines for fiber, trans fatty acids and alcohol was lower. Abstract: Olfaction plays a major role in food intake regulation. Losing the sense of smell might therefore affect eating behavior. This study investigated food preferences and intake in individuals suffering from self-reported smell loss with an online survey. Members of the Dutch Anosmia Foundation (DAF) performed the Macronutrient and Taste Preference Ranking Task (n = 71) to measure preference for foods high in fat, carbohydrates or protein and low energy foods, and for sweet and savory tastes. To assess dietary intake, adherence to the Dutch Dietary Guidelines for consumption of vegetables, fruit, fiber, fish, saturated fat, trans fatty acids, salt and alcohol was measured (n = 105). Results of the DAF participants were compared to local cohort groups. Both the control and DAF participants showed the lowest preference for carbohydrate-rich foods and highest preference for low-energy foods. Participants suffering from congenital smell loss showed an aberrant pattern, with a higher preference for fat. The total adherence score to the Dutch Dietary Guidelines was similar for the control and DAF group, but adherence scores for fiber, trans fatty acids and alcohol were lower in DAF participants. Overall, no major significant differences in food preferences and intake were found for participants who lost their sense of smell during life. Participants suffering from congenital smell loss did show changes in food preferences, suggesting they are potentially more taste-oriented during eating. Together these results show the importance of tailored advice on dietary intake for this patient group.